EVALUASI KEPATUHAN PETUGAS DALAM TATALAKSANA PNEUMONIA DI KABUPATEN TOLITOLI - Abd Rahman; Mohammad Hakimi; Rina Triasih (JURNAL KESEHATAN REPRODUKSI, 2015)
EVALUASI KEPATUHAN PETUGAS DALAM TATALAKSANA PNEUMONIA DI KABUPATEN TOLITOLIAbd Rahman1, Mohammad Hakimi2, Rina Triasih3ABSTRACTBackground: The infant mortality rate in Central Sulawesi Province is 52 per 1000 live births, which isthe fifth highest in Indonesia. The high rate of morbidity and mortality of acute respiratory infection andpneumonia in children under five in Tolitoli District in past year related to the implented efforts triandsARI eradication program. This is indeed related to how officers comply with pneumonia managementcorrectly.Objective: To evaluate officers’ compliance in implementing pneumonia manager Tolitoli Distric.Method: This was an observational study with cross-sectional study design, using quantitative approach,Data were collected through observation and interview using standardized questionnaire by tramednurses. Officer who handled pneumonia program in Tolitoli District and those in Publich Health Centreswere recruited as subjects.Result and Discussion: One hundred and nineteen subjects were recruited to this study. The percentaseof officers who complied with pneumonia management was 69%. The result of multivariate analysis thatwas training increased officers’ compliance in pneumonia management which was adjusted to education,knowledge and length of work had a significant relationship (PR: 1.79; 95% CI: 1,38 – 2,33) and theincreased value R2 of 6.3%, it mean.Conclusion: Trained officers were more compliant than untrained officers with the prevalence risk of1.79 times. Education, knowledge, and length of working service were related to officers’ compliance inpneumonia management.Keywords: training, officers’ compliance in pneumonia managementABSTRAKLatar belakang: Angka kematian bayi di Propinsi Sulawesi Tengah sebesar 52 per 1000 kelahiran hidupdan menempati urutan kelima tertinggi di Indonesia. Tingginya angka kesakitan dan angka kematian balitaakibat pneumonia di Kabupaten Tolitoli dalam beberapa tahun terakhir tidak terlepas dari seberapa jauhupaya program pemberantasan penyakit ISPA telah dilaksanakan. Hal ini sangat terkait dengan bagaimanakepatuhan petugas dalam melakukan tata laksana pneumonia secara tepat.Tujuan: Diketahuinya kepatuhan petugas dalam melakukan tatalaksana pneumonia di Kabupaten Tolitoli.Metode: Penelitian ini merupakan jenis penelitian observasional dengan rancangan cross sectional denganmenggunakan pendekatan kuantitatif. Data dikumpulkan melalui observasi dan wawancara dengan subyekpenelitian dengan menggunakan lembar observasi dan kuesioner.Hasil dan Pembahasan: Sebanyak 119 subyek diikutkan dalam penelitian ini. Rata-rata petugas yang patuhterhadap tata laksana pneumonia sebesar 69%. Hasil analisis multivariat menunjukkan bahwa variabelpelatihan dan kepatuhan petugas dalam tatalaksana pneumonia dengan mengikutsertakan variabel pendidikan, pengetahuan dan masa kerja untuk dianalisis secara bersama mempunyai hubungan yangsignifikan ((RP;1,79, IK 95%; 1,38 – 2,33) dan peningkatan nilai R2 sebesar 6,3%Kesimpulan: Petugas yang telah dilatih lebih patuh dibanding petugas yang belum dilatih dengan risikoprevalensi 1,53 kali. Faktor pendidikan, pengetahuan dan masa kerja berhubungan secara bermaknadengan kepatuhan petugas dalam tataksana pneumonia.Kata kunci: pelatihan, Kepatuhan petugas tatalaksana pneumonia1 Tolitoli Faculty of Medicine and Health Science2 Maternal and Child Health-Reproductive Health Graduate Program, FK-UGM3 Pediatric Department, Dr. Sardjito General Hospital, Yogyakarta